FEATURES OF USING SOCIAL NETWORKS TO ACHIEVE CYBERINFLUENCE - Samchyhsyn, Oleksii; Nosova, Hanna (Ukrainian Information Security Research Journal, 2023)
In the modern information society, such a type of virtual communities as social networks has become widespread. The task of such social Internet services is to provide users with all possible ways of interacting with each other. Social networks, in addition to fulfilling the functions of supporting communication, exchange of opinions, meet their professional needs, political ambitions, satisfaction of their interests in art, permission and preservation of information by members of the virtual community, increasingly become objects and use of informational and cybernetic influence. Monitoring of open sources, accounts, groups, application of social engineering methods and realization of cybernetic influences are considered the main stages of conducting cybernetic operations in social Internet services that use them. In the conditions of the Russian Federation's large-scale war against Ukraine, which has a largely hybrid component, digital means of mass communication and social Internet services are widely used by the enemy to exert destructive informational, psychological and cybernetic influence on the military-political leadership, personnel and population of the country as a whole. Therefore, it is relevant to analyze the vulnerabilities of an individual user, depending on the information posted by him in social networks, and to develop methods of protection against destructive cybernetic influences, so that it is possible to create an effective system for detecting and countering them in the future.